Comparative study on the development characteristics of Chinese male table tennis technique and tactic across the Olympic period - Jia, H.; Li, Z.; Tang, H. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
The purpose of the study: Since 2010, table tennis movement into inorganic era, during the London 2012 Olympic Games baptism, the inorganic glue water brings to the table tennis what kind of change? Through the comparative study of nearly five years of four excellent players technical and tactical development characteristics, to explore the influence of. In view of influence of both new material and inorganic glue ball on the table tennis is similar, and provides appropriate reference effect on the next step. Research methods: 1.video statistics using the "three sections evaluation" of the four athletes in recent five years of 131 matches for the related data statistics. 2. The logic analysis method combined with the movement rule of table tennis ball and changes the rules of the impact, the technical and tactical characteristics of four world champion is analysed. 3. Comparative analysis of the statistical results of the four world champion 3, comparative law and tactical and technical characteristics of the overall variation characteristics and evaluation standards, draw a conclusion. Results and discussion: Separately from the hair rob segment tactical index, then grab the period of technical and tactical index and the three aspects of the technical and tactical stalemate segment index, individual technical and tactical development characteristics of men's table tennis of China's overall technical and tactical development characteristics and four outstanding athletes to compare and analyse the similarities and differences between the object of study, a profound analysis in these three aspects. The research conclusion: The overall level of competitive development of complementary features, more stable; attack section technique and tactics level in good range, has a larger promotion space; then grab the most prominent section of technical and tactical level, no significant difference between the two kinds of style, a means of diagnosis based on three segment index need further improvement; stalemate weak link segment still need to strengthen technical and tactical level.